Acute effect of standard heparin versus low molecular weight heparin on oxidative stress and inflammation in hemodialysis patients - Poyrazoglu, Orhan Kursat; Dogukan, Ayhan; Yalniz, Mehmet; Seckin, Dilara; Gunal, Ali Ihsan (Taylor & Francis Ltd, 2006)
Objective. Atherosclerotic cardiovascular diseases caused by traditional and non-traditional risk factors are the most common cause of morbidity and mortality in hemodialysis patients. Recently, much interest has been focused on non-traditional factors, such as oxidative stress, inflammation, and endothelial dysfunction. Hemodialysis patients are not only exposed to oxidative stress but also to inflammation. Although anticoagulants are the most frequently used drugs in hemodialysis patients, their effect upon oxidative stress and inflammation in dialysis patients are still unknown. Methods. Thirty-three hemodialysis patients were randomized into three groups. Group 1 received standard heparin while group 2 received low molecular weight heparin during the dialysis therapy. Group 3 (control group) did not receive any anticoagulant agent. Investigators were blinded to the therapy. Serum concentrations of oxidative stress and inflammation markers, including C-reactive protein, tumor necrosis factor alpha, superoxide dismutase, and malondialdehyde, were measured before and after dialysis session. Results. The oxidative stress and inflammation markers were significantly increased in groups I and 3 (p < 0.05 for each) compared to their baseline values. In contrast, baseline and end-treatment values of the oxidative stress and inflammation markers were comparable in the group 2 (p > 0.05). Conclusion. These findings indicate that the type of anticoagulants may take a role in the acute effect of hemodialysis upon oxidative stress and inflammation markers. A comparison of the groups revealed that low molecular weight heparin decreased the oxidative stress and inflammation, whereas standard heparin increased the oxidative stress and inflammation. Low molecular weight heparin appears to have an additive benefit for hemodialysis patients.
1st John H Dirks Chronic Renal Disease Prevention on Prevention Strategies for Chronic Kidney Disease in Latin America -- NOV 21-23, 2005 -- Vallarica, CHILE
Keywords: hemodialysis; low molecular weight heparin; standard heparin; oxidative stress; inflammation